UJI KINERJA FREEZER MENGGUNAKAN DIMETHYL ETHER SEBAGAI REFRIGERAN PENGGANTI R134a - Mawaddati Sofwah Utami; Mitrakusuma, Windy Hermawan; Simbolon, Luga Martin; Rosulindo, Parisya Premiera (LPPM, Universitas Negeri Jakarta, 2023)
R134a is widely used as a refrigerant in refrigeration systems, but this refrigerant has an impact on increasing global warming. This impact can be reduced by using dimethyl ether as an alternative refrigerant to replace R134a. In this research, the performance of dimethyl ether was tested as a substitute refrigerant for R134a in refrigeration system applications in the form of freezers. Tests were carried out by comparing the performance of the freezer when using refrigerant R134a and using dimethyl ether refrigerant. The use of dimethyl ether in the test was varied based on mass, namely 60 grams, 70 grams and 80 grams, or in percentages as much as 30%, 46.7% and 53.3% of the total mass of R134a. The results of this test indicate that the COP value for freezer performance is higher when using dimethyl ether than when using R134a, the efficiency is higher than refrigerant R134a, and the compressor power is lower than R134a. Testing for variations in the mass of dimethyl ether that approached the condition of R134a was at a mass of 70 grams, so that the amount of refrigerant filled with dimethyl ether as a substitute for R134a was reduced to 46,7% of the amount of R134a.